Dietary glutamine, glutamate and mortality: two large prospective studies in US men and women - W. Ma; Heianza, Y.; Huang, T.; T. Wang; Sun, D.; Zheng, Y.; Hu, F. B.; Rexrode, K. M.; Manson, J. E.; Qi, L. (Int J EpidemiolInt J EpidemiolInt J Epidemiol, 2018)
Background: Emerging studies have related circulating glutamine metabolites to various chronic diseases such as cardiovascular disease and cancer; diet is the major source of nutrients involved in glutamine metabolism. However, it remains unknown whether dietary intakes of glutamine, glutamate,and their ratio are related to total and cause-specific mortality. Methods: We followed 74 082 women from the Nurses' Health Study (1984-2012) and 42 303 men from the Health Professionals Follow-up Study (1986-2012), who were free of cardiovascular disease and cancer at baseline. Diet was updated every 2 to 4 years by using validated food frequency questionnaires. The content of glutamine and glutamate in foods was calculated based on protein fractions generated from gene sequencing methods and adjusted for total energy intake. Results: We documented 30 424 deaths during 2 878 344 person-years of follow-up. After adjustment for potential confounders including lifestyle and dietary factors, higher intakes of glutamine and glutamine-to-glutamate ratio were associated with significantly lower risk of total and cause-specific mortality. Compared with people in the lowest quintile of dietary glutamine-to-glutamate ratio, the pooled hazard ratio (HR) in the highest quintile was 0.87 [95% confidence interval (CI): 0.84, 0.91; P for trend < 0.001) for total mortality, 0.81 (95% CI: 0.75, 0.88; P for trend < 0.001) for cardiovascular mortality, and 0.93 (95% CI: 0.87, 0.99; P for trend = 0.01) for cancer mortality. Conclusions: We found dietary glutamine and glutamine-to-glutamate ratio were inversely related to risk of mortality, particularly cardiovascular mortality, independent of other dietary and lifestyle factors, in US men and women.